The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00432-013-1568-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transarterial chemoembolisation (TACE) combined with endovascular implantation of an iodine-125 seed strand for the treatment of hepatocellular carcinoma with portal vein tumour thrombosis versus TACE alone: a two-arm, randomised clinical trial

Abstract: Transarterial chemoembolisation combined with the endovascular implantation of an iodine-125 seed strand is feasible, safe and effective in the treatment for hepatocellular carcinoma with PVTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 24 publications
4
57
0
Order By: Relevance
“…Endovascular implantation of 125 I seed strands was performed as previously described [15]. Conventional chemoembolization was performed using doxorubicin (Pfizer, New York, NY, USA) mixed with 5–20 mL of iodized oil (Lipiodol Ultra-Fluide, Laboratoire Guerbet, Villepinte, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular implantation of 125 I seed strands was performed as previously described [15]. Conventional chemoembolization was performed using doxorubicin (Pfizer, New York, NY, USA) mixed with 5–20 mL of iodized oil (Lipiodol Ultra-Fluide, Laboratoire Guerbet, Villepinte, France).…”
Section: Methodsmentioning
confidence: 99%
“…125 I seed implantation was attempted to treat HCC with PVTT and achieved excellent therapeutic efficacy [15] with a good safety profile [16]. The combination of radiation therapy and TACE has been explored before [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…This combination therapy also improved the reperfusion rate of portal vein significantly [51]. Another study showed I 125 seeds followed by TACE significantly improved the median survival and progression free survival rates when compared to I 125 alone ( P = 0.037 and 0.002, respectively) [52].…”
Section: Nonsurgical Therapiesmentioning
confidence: 99%
“…[88] (evidence level 2); (2) TACE in combination with radiation therapy [84] (evidence level 2), which could be selectively used for patients with tumor emboli in the portal trunk and inferior vena cava or localized large HCC after TACE; (3) TACE in combination with surgical resection, which should be recommended for large HCCs that have shrunk after TACE and are suitable for surgical resection [88] (evidence level 3); and (4) TACE in combination with systemic treatment, including molecular target drugs, arsenic trioxide, radiolabeled drugs, gene therapy, immunotherapy, and systemic chemotherapy [93, 94]. …”
Section: Treatmentmentioning
confidence: 99%
“…(2) The tumor emboli in the portal vein trunk can be effectively treated to resume blood flow by portal vein stenting and I-125 seed strip or I-125 seed portal vein stenting [88] (evidence level 2).…”
Section: Treatmentmentioning
confidence: 99%